Patients' subjective assessment of the duration of cataract surgery: a case series. Issue 5 (8th May 2013) - Rothschild, Pierre-Raphael; Grabar, Sophie; Le Dû, Brivael; Temstet, Cyril; Rostaqui, Olga; Brézin, Antoine P
Abstract : Objectives: Surgery duration is a source of preoperative anxiety for patients undergoing cataract surgery. To better inform patients, we evaluated the agreement between objective and patient-perceived surgery durations. Design: Case series. Setting: Public teaching university hospital (Paris, France). Participants: During the study period, 368 cataract surgery cases performed on 285 patients were included, 85 cases were excluded from the final analysis. All patients who had uneventful phacoemulsification were included. Cases with any significant intraoperative adverse event or cases requiring additional anaesthesia other than topical were excluded. Resident performed cases were also excluded. Primary and secondary outcomes: Procedures were timed (objective duration) and patients were asked, immediately afterwards, to assess the duration of their surgery (patient-assessed duration). The agreement between objective and patient-assessed durations as well as influencing factors was studied. Results: Mean objective duration (13.9±5 min) and patient-assessed duration (15.3±6.9 min) were significantly correlated (Spearman's r=0.452, p<0.0001). Furthermore, Bland-Altman analysis and the intraclass correlation coefficient (0.341, 95% CI 0.23 to 0.44) were quite in agreement. On univariate analysis, senior-performed procedures were significantly shorter than those performed by juniors (13.4 vs 17.8 min, p=0.0001). Pain was recorded as 'no sensation' (31.5% of the cases), 'mild sensation' (41%), 'moderate pain' (23.3%), 'intense pain' (3.5%) and 'unbearable pain' (0.7%). Groups with high pain score had significantly longer procedures (p<0.001). Multivariate analysis revealed that the only independent factors associated with both the objective and patient-assessed durations of surgery were surgeon's experience and pain-score. Conclusions: In our study, patients' estimated and real duration of the surgery showed moderate agreement, suggesting that emotions associated with eye surgery under topical anaesthesia did not dramatically hinder the patients' perception of time. However, the benefit of preoperative counselling regarding the duration of surgery will need further evaluation.